PENERAPAN COMMUNITY BASED TOURISM (CBT) DALAM PENGEMBANGAN DESA WISATA DI DESA SEKAPUK KECAMATAN UJUNGPANGKAH KABUPATEN GRESIK - Maslakhatun Niswah; Tukiman Tukiman (Universitas Halu Oleo, 2021)
The COVID-19 pandemic has had a significant impact in various fields, especially in the tourism sector which also has an impact on the country's economy. The central and local governments are currently doing various methods, including the Sekapuk Village Government. In the midst of the current pandemic, Sekapuk Village has succeeded in increasing village income as a source of economic resilience from tourism. Sekapuk Village has also achieved various achievements. This is inseparable from the support from the community. The purpose of this research is to see the application of the principles of Community Based Tourism (CBT) in the Development of Tourism Villages in Sekapuk Village, Ujungpangkah District, Gresik Regency. This type of research used in this research is descriptive qualitative. The results of this study indicate that the implementation of CBT in Sekapuk Village has not been implemented as a whole. In the planning principle, the community has not played an active role. Then on the principle of implementation, the community has played an active role and participated in tourism ownership. Furthermore, the impact and benefits have been felt by the community significantly